2015
DOI: 10.1111/bld.12130
|View full text |Cite
|
Sign up to set email alerts
|

Training a family in physical interventions as part of a positive behaviour support intervention for challenging behaviour

Abstract: Accessible summary• Dylan has a learning disability and challenging behaviour.• He was hurting himself and other people.• We trained his family to help them cope safely when Dylan was aggressive.• Now fewer people are getting hurt when Dylan gets angry and his parents know more about how to help him. SummaryBetween 10% and 15% of people with a learning disability have behaviour that challenges others, and half of these people live within the family home (Emerson et al., Research in Developmental Disabilities,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…This finding supports the study established that the environmental and social enablers, including inclusivity in activities by their communities, can determine the children’s social interaction [ 48 ]. Congruent with these findings, previous results found that information given to the family caregivers on the children’s behaviour, including emotional changes and aggression, improved their skills to handle the child and further increased feelings of competence and confidence [ 49 ].…”
Section: Discussionmentioning
confidence: 90%
“…This finding supports the study established that the environmental and social enablers, including inclusivity in activities by their communities, can determine the children’s social interaction [ 48 ]. Congruent with these findings, previous results found that information given to the family caregivers on the children’s behaviour, including emotional changes and aggression, improved their skills to handle the child and further increased feelings of competence and confidence [ 49 ].…”
Section: Discussionmentioning
confidence: 90%
“…Training has also been shown to increase the confidence of staff in adult services supporting autistic individuals (McDonnell et al, 2008;McDonnell, 2010). A single case study applied the Low Arousal Approach to an individual family (Shinnick and McDonnell, 2003;Hewitt et al, 2015). In this study, the families were taught the principles of the Low Arousal Approach and some physical interventions.…”
Section: Introductionmentioning
confidence: 99%